PENGAMBILAN KEPUTUSAN KONSUMEN DALAM MEMILIH TEMPAT BERBELANJA DI KECAMATAN MALALAYANG KOTA MANADO - Tri Kristiono; Ventje V. Rantung; Jenny Baroleh; Rine Kaunang (COCOS, 2015)
ABSTRACK Tri Kristono, Consumer Decision Making in Choosing Where to Shop in District Malalayang Manado City (under the guidance of V. Ventje Rantung as chairman, Jenny Baroleh and Rine Kaunang as a ember). The purpose of research is to know how the decision making process of consumers in choosing where to shop in District Malalayang Manado City, and want to know the place where the most dominant shopping visited by Malalayang public. Data collected for three months, since of January until of March 2015. Primary data obtained directly through in-depth interviews based on a questionnaire that give to consumers (public Malalayang). Secondary data obtained through agencies associated with this research.Â  Samples by accidental sampling technique with respondents as many as 180 customers. The analysis is qualitative analysis. The results showed that the consumer decision in choosing where to shop be some factor that is affected by the quality, convenience, price, service, distance, income, and prestige. Consumer decision-making process starts from the introduction of needs, information search, evaluation of alternatives and decision selector. Prestige factor is the biggest factor affected consumers in making decisions. And the dominant place visited by people Malalayang is Freshmart superstore